Remarks at the International Industrial Conference, San Francisco, September 21, 1981 - Clausen, A. W. (2016)
A. W. Clausen, President of the World Bank Group, discusses the major economic challenges confronting the interdependent world, the role transnationals can play in helping to overcome them, and the effects of the rampant and stubborn inflation that has characterized the past dozen years.